NOTES ON TAXONOMY AND NOMENCLATURE IN THE GENUS LYGODIUM (SCHIZAEACEAE) - A. H. G. ALSTON, R. E. HOLTTUM (BRIN Publishing (Penerbit BRIN), 1959)
Due to various causes, the early history of both taxonomy and no menclature in the genus Lygodium is very confused. As a result,a numberof problems arise which need fuller discussion than is possible in Flora Malesiana.Such problems are here discussed, concerning most of the species native in Malaysia.The new combination Lygodium auriculatum (Willd.) Alston is published, and a new typification of the species Ophioglossum scandens L. is proposed.